PENGARUH KESADARAN LINGKUNGAN TERHADAP PERSEPSI KONSUMEN DAN NIATBELI PRODUK LAMPU LED PHILIPS DIKOTA DENPASAR - Krisnanda, A.A. Ngurah Bagus Jaya; Nurcaya, I Nyoman (E-Jurnal Manajemen; Vol 8 No 2 (2019)DO - 10.24843/EJMUNUD.2019.v08.i02.p19, 2019)
ABSTRACT The purpose of this research is to explain the influence of environmental awareness to consumer perception on Philips LED lighting product, to know the influence of environmental awareness and consumer perception on buying intention of Philips LED Lights product, and to know consumer perception role in mediating environmental awareness variable to purchase product intention Lamp Philips LED. The population in this study are consumers who have the desire to buy Philips LED lights in the city of Denpasar. The sampling technique used is purposive sampling method. The number of samples used in this study as many as 110 samples. Analysis technique in this research using path analysis technique (Path Analysis). The results showed that environmental awareness has positive and significant impact on consumer perception on Philips LED Lights product in Denpasar City. Environmental awareness has a positive and significant impact on purchase intention of Philips LED Lights in Denpasar City. Consumer perceptions have a positive and significant effect on purchase intention of Philips LED Lights in Denpasar City. Consumer perceptions positively and significantly mediate the influence of environmental awareness on purchasing intentions of LED lighting products in Denpasar City. Keywords: Environmental awareness, Consumer perception, Intention to buy